The effects of return migration on political participation in Puerto Rico - Ramos, Carlos Vargas (ProQuest LLC, 2000)
This study analyzes data from a survey conducted in a Puerto Rican municipality in order to gauge the extent to which the political socialization of migrants in the receiving society affected their political participation upon their return to the polity of origin. The study tested the hypothesis that the relative depolitization of Puerto Rican migrants in the United States would lead to a decline in their political participation once they returned to the island. Measures of electoral and nonelectoral participation in both Puerto Rico and the United States were collected. The results show that, while there was a very slight decline in some measures of political participation as a result of the migration experience, substantively the relative depolitization which Puerto Ricans experienced while in the United States did not manifest itself upon their return. The analysis in effect confirms the null hypothesis which characterizes the political experience of these migrants as one of "dormancy" while sojourning. The results moreover substantiate arguments prevalent in the political socialization literature that note how patterns of political behavior learned in childhood persist in adulthood; albeit without foreclosing the possibility of further learning later in life. Furthermore, the experience of these migrants shows how sensitive and adaptable people are to changing political institutions. Lastly, the political dormancy which characterizes these migrants speaks to how the institutional arrangement and practices in the United States hinder the incorporation and engagement of actors newly arrived in the political system.